Twenty Years of the Centro de Estudos Galegos at the Universidade do Minho (1997-2017): Balance and Future Perspectives - Groba Bouza, Fernando; Basanta Llanes, Noemi; Dono López, Pedro (Madrygal. Revista de Estudios Gallegos, 2019)
Since the year of its creation, in 1997, through an agreement between the Xunta de Galicia and the Universidade do Minho, the Centro de Estudos Galegos has undergone a process of progressive insertion and consolidation not only in the academic context of the university of Braga, but also in different areas of Miñota society, particularly in sectors linked to cultural action. The work carried out by the different readers of the Center has contributed (and contributes) not only to bring the Galician linguistic and cultural reality closer to the context of the north of Portugal, where paradoxically it is/was quite unknown, but also to favor the interaction between cultural agents from both sides of the river Miño/Minho. We address in this contribution the evolution of the presence of the teaching of the Galician language and culture in the UMinho, from the university extension courses to the options that allow to reach the students of multiple degrees of the academic offer of the institution, or to the different outreach activities organized, often in partnership with relevant cultural actors from the city of Braga, such as the Rádio Universitária do Minho (RUM) or the asociación cultural Canto d’Aqui: the radio program Galiza Mais Perto (RUM 97.5), Semana Cultural Convergências Portugal-Galiza, Dia da Galiza em Braga or Encontro Minho-Galiza are examples of this. One aspect that may have been paid less attention, that of research, should assume a greater role in the coming years, because it also warns of the need to strengthen links in the scientific field.